(untitled) (Inženierzinātņu un augstskolu vēsture, 2018)
Rakstā aplūkota inženiera Mihaila Doļivo-Dobrovoļska (1862– 1919) saistība ar Latviju un studijām Rīgas Politehnikumā (1878–1881), kā arī dots ieskats viņa laikabiedru gaitās. M. Doļivo-Dobrovoļskis ir pasaulē pazīstams kā trīsfāžu maiņstrāvas izgudrotājs, viņa devums elektroenerģētikā tika novērtēts jau viņa dzīves laikā, kā arī netiek aizmirsts joprojām. 2012. gadā viņam post mortem piešķirts RTU Goda biedra nosaukums. Inženiera dzīves darbības izpētē izmantoti arhīvu dokumenti un bibliotēku krājumi, dodot iespēju rakstā iekļaut precizējumus attiecībā uz Doļivo-Dobrovoļsku dzimtu, kā arī izsekot iemesliem tās godināšanai Latvijā.In Remembrance of the 155th birthday of Doliwo-Dobrowolski - Student of the Riga Polytechnic and Honorary Member of Riga Technical UniversityThe article describes the activities of the famous engineer, electrician and inventor Mikhail Doliwo-Dobrowolski (1862-1919) in the context of his studies at the Riga Polytechnic (1878–1881) and his life in the Baltic provinces of Russia. At the end of the 19th century, engineering education could be obtained at the Riga Polytechnic, thus many of his contemporaries who studied at the Riga Polytechnic and were Doliwo-Dobrowolski’s colleagues at Allgemeine Elektrizitäts Gesellschaft (AEG). Doliwo-Dobrowolski is a co-inventor of threephase electrical systems. He developed the three-phase generator and threephase motor and is a world known scientist. His contribution to the development of electrical engineering was highly esteemed already during his lifetime. The significance of his work reaches out to the present days. In 2012, in celebration of Doliwo-Dobrowolski’s 150th birthday, Riga Technical University, former Riga Polytechnic, elected him (post mortem) «Honorary Member» for his scientific achievements. In 2013, a plaque commemorating Doliwo-Dobrowolski’s stay in Riga and his scientific achievements was set up on the ground floor of the administrative building of RTU at 1 Kaļķu Street in Riga. To research the life of Doliwo-Dobrowolski, his family and the time of his stay in Riga, the author studied the resources in archives and libraries.Keywords: Mikhail Doliwo-Dobrowolski, electrotechnics at Riga Politechnic, Honorary Member of RTU.Алида Зигмунде. Студенту Рижского политехнического училища и почетному члену Рижского технического университета Михаилу Доливо-Добровольскому – 155В статье автор рассказывает о известном во всем мире изобретателе трехфазного переменного тока Михаиле Доливо-Добровольском (1862–1919). В Рижском Политехническом училище он изучал химию (1878–1881), но учебу не окончил. В 1883 году он начал учебу в Дармштате, Германии и стал специалистом электротехники. В 1885/86 учебном году в программу Рижского Политехнического училища была включена и электротехника. Несколько современников М. Доливо-Добровольского также были связаны с электротехникой, некоторые бывшие рижские студенты работали в той же компании – AEG. Основную часть деятельности он был связан с Германией и Швейцарией. Сделанное М. Доливо-Добровольским было признано уже при его жизни, но не забыто и сейчас. К его стопятидесятилетнему юбилею в 2012 году ему было присвоено звание Почетного члена Рижского технического университета (РТУ; post mortem). В 2013 году в административном здании РТУ на улице Калькю 1 была открыта мемориальная доска М. Доливо-Добровольскому. При исследовании были использованы документы архивов и библиотек, в которых не нашлось подтверждений о его политической деятельности. Полиция разыскивала кого-то с фамилией Добровольский, но не конкретно Михаила. Ключевые слова: Mихаил Доливо-Добровольский, электротехника в Рижском политехникуме, почетные члены РТУ.